Los Gastos Operacionales para medir la eficiencia mediante el modelo de Análisis Envolvente de Datos en las COAC del segmento 1 y 2, provincia de Chimborazo 2017-2021. - Rea Chucuri, Kelvin Brayan (2024)
ABSTRACT: The present research “The Operational Expenses to measure efficiency through the Data Envelopment Analysis model in the COACs of segment 1 and 2, province of Chimborazo 2017-2021”, was developed with the main objective of Analyzing the operational expenses to measure efficiency through the Data Envelopment Analysis model, using a quantitative methodology itself that allowed the collection of data through the financial statements published by the Superintendence of Popular and Solidarity Economy (SEPS), where the data analysis was executed for the estimation of efficiency with the implementation of the tool, Data Envelopment Analysis (DEA), considering as inputs to personnel expenses, expenses in services and other expenses; The outputs were interest income, service income and other operating income, making it possible to determine the efficiency of the Credit Unions in segments 1 and 2, reflecting an average efficiency of 97% for Personnel Expenses and Interest Income, and an average efficiency of 91% for Service Expenses and Service Income, In segment 2, Personnel Expenses and Interest Income had an average efficiency of 70%, while Service Expenses and Service Income had an average efficiency of 45%, and Other Expenses and Other Operating Income had an average efficiency of 36%.